Three Complex alleles associated with N1303K mutation and their molecular consequences: Three complex alleles of CFTR gene - Farhat, Raëd; EL-Seedy, Ayman; Pasquet, Marie-Claude; Corbani, Sandra; Megarbané, André; Kitzis, Alain; Ladeveze, Véronique (Cellular and Molecular Biology, 2022)
Cystic Fibrosis (CF) in Arab Mediterranean countries has a different CFTR mutational profile if compared either to Caucasians or in the Arabian Peninsula. The c.3909C>G (N1303K, p.Asn1303Lys) mutation of the Cystic Fibrosis Transmembrane Conductance Regulator gene (CFTR). This mutation represents a higher frequency in the Mediterranean countries in association with different polymorphisms or mutations in cis position constituting various complex alleles. N1303K mutation induces many phenotypes, especially pancreatic insufficiency from mild to severe and it is associated in cis with other polymorphisms. The aim of this investigation is therefore to screen complex alleles carrying N1303K mutation among Lebanese, Egyptian and French patients. All exons of the CFTR and their flanking regions were performed by PCR amplification, followed by automated direct DNA sequencing. Two complex alleles are more frequent corresponding to Wild Type and mutated haplotype. Besides that two other very rare complex alleles have been detected, one in Egyptian and French samples, and then another one in Lebanon samples. We have studied their impact on the CFTR mRNA splicing using a minigene strategy. Constructs containing wild-type and mutant CFTR cloned into the pTBNdeI hybride minigene have been expressed in HeLa, HT29 and HEK293 cells. RT-PCR analysis of mRNA using β-globin-specific primers revealed that N1303K and the polymorphisms associated with cis induce weak abnormal splicing and a modification of the quality and the quantity of CFTR protein. These different associations of identified polymorphisms with N1303K in cis could have an impact on the severity of the disease.